Sold on a monday ebook A novel. - McMorris, Kristina (2018)
A NEW YORK TIMES BESTSELLER WITH MORE THAN A MILLION COPIES SOLD—Sold on a Monday is the unforgettable book-club phenomenon, inspired by a stunning piece of Depression-era history.  "A masterpiece that poignantly echoes universal themes of loss and redemption...both heartfelt and heartbreaking."—Pam Jenoff, New York Times bestselling author of The Orphan's Tale 2 CHILDREN FOR SALE. The sign is a last resort. It sits on a farmhouse porch in 1931, but could be found anywhere in an era of breadlines, bank runs and broken dreams. It could have been written by any mother facing impossible choices. For struggling reporter Ellis Reed, the gut-wrenching scene evokes memories of his family's dark past. He snaps a photograph of the children, not meant for publication. But when it leads to his big break, the consequences are more devastating than he ever imagined. Inspired by an actual newspaper photograph that stunned the nation, Sold on a Monday has celebrated five months on the New York Times bestsellers list and continues to especially captivate fans of Lisa Wingate's Before We Were Yours and Kristin Hannah's The Four Winds. Look for the new novel by Kristina McMorris, The Ways We Hide, a sweeping World War II tale of an illusionist whose recruitment by British intelligence sets her on a perilous, heartrending path.